PENGARUH FINANCIAL KNOWLEDGE DAN PARENTAL INCOME TERHADAP FINANCIAL MANAGEMENT BEHAVIOUR MAHASISWA JURUSAN MANAJEMEN UNIVERSITAS KRISTEN MARANATHA BANDUNG - Melvin, Melvin; Winarto, Jacinta (Catholic University Musi Charitas, 2024)
The purpose of this study was to examine and analyze the influence of Financial Knowledge and Parental Income on the Financial Management Behavior of students majoring in management at Maranatha Christian University, Bandung. This research is a quantitative research. Sampling was carried out purposively on 56 students majoring in management at Maranatha Christian University, Bandung. The results of the study with multiple regression analysis show that Financial Knowledge has an effect on Financial Management Behavior, while Parental Income has no effect on Financial Management Behavior. Financial Knowledge and Parental Income together influence Financial Management Behavior. It is recommended for future researchers to add or substitute other variables to replace the income variable, and add a larger and more diverse sample size, not only among students. The implication of this research is that students majoring in management need to apply financial knowledge on a daily basis and in financial planning courses there is a need to practice financial knowledge